Media Lagu terhadap Kemampuan Menyimak - Dewi Ratna sari; Misnah Mannahali (Universitas Negeri Makassar, 2024)
Abstract. The purpose of this study was to dermine the effectiveness of the use of song media on the listening skills of class XI SMA Kartika XX-I Makassar. this type of research is pre-experimental one group pre-test/post-test design. The total sample used in this study was 18 students of class XI IPS 2. The research data were analyzed using the T-test. The results of data analysis shwed that t count 13,36 > t table 2,120 at significant level of 0,05. These results indicate that song media is effective on listening skilss. Keywords: Effectiveness, Listening, Song Media.